PENCEGAHAN NYERI KEPALA DAN DISABILITAS LEHER MELALUI INTERVENSI MC KENZIE NECK EXERCISE DAN EDUKASI POSISI KERJA ERGONOMIS - Saraswati, N.L.P.G.K.; Saraswati, P.A.S.; Kamayoga, I.D.G.A.; Santika, I.W.M. (Buletin Udayana Mengabdi, 2023)
The reason behind the importance of this service is based on surveys, and the results of previous studies of musculoskeletal complaints, especially the prevalence of cases of pain due to headaches and neck disabilities in workers who work in front of computers reaching 66%, this complaint certainly has an impact on decreasing productivity and work quality. Office workers do not yet have the knowledge they can do to prevent and reduce complaints of pain due to headache and neck disability. 2) providing physiotherapy services in the form of exercise therapy, namely Mc Kenzie Neck Exercise, (3) providing educational media in the form of pamphlets to service participants. The series of service processes are carried out by means of direct visits to the place of service at SMA (SLUA) ??Saraswati 1 Denpasar. The service participants were 90 people consisting of 48 men (53.3%) and 42 women (46.7%). The age range of service participants is 18 – 59 years, where the average value is (36.02±12.19). The results of the examination of musculoskeletal complaints with nordic body maps (NBM) were dominated with a score of 51 which interpreted as moderate pain, the mean value of NBM measurement was (46.05±14.8). Keywords: headache, neck disability, musculoskeletal disorders, nordic body maps (NBM)